2016
DOI: 10.1002/apj.2048
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of methyl orange dye by ZnO loaded onto carbon xerogels composites

Abstract: The present paper studies the photocatalytic behavior of pure zinc oxide (ZnO) and ZnO loaded onto carbon xerogel as a substrate. These samples were prepared by a sol‐gel process in presence of either an ionic liquid or an alcohol such as 1‐ethyl‐3‐methylimidazolium trifluoromethylsulfonate (A) or isopropanol solvent (B) to produce ZnO‐CX‐A and ZnO‐CX‐B photocatalysts, respectively. Transmission electron microscopy and X‐ray diffraction proved that ZnO particles were prepared as nanoflakes‐like with amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…P = O, P–O–P, P = OOH, P–O–C) and C–O groups are located between 1300 and 1000 cm −1 (Bandosz and Ania, 2006; Puziy et al., 2002), consecutively. It is observed that a shoulder peak at 450 cm −1 is obtained in FTIR spectrum of ZnO-AC indicating the presence of few free ZnO (Farag et al, 2016; Pulido et al., 2009). Additionally CeO 2 and ZnO catalysts expanded the absorption bands at 3430 cm −1 (–OH), 1625 cm −1 (COOH), and 1082 cm −1 (C–O), confirming the interaction of ceria and ZnO with these functional groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P = O, P–O–P, P = OOH, P–O–C) and C–O groups are located between 1300 and 1000 cm −1 (Bandosz and Ania, 2006; Puziy et al., 2002), consecutively. It is observed that a shoulder peak at 450 cm −1 is obtained in FTIR spectrum of ZnO-AC indicating the presence of few free ZnO (Farag et al, 2016; Pulido et al., 2009). Additionally CeO 2 and ZnO catalysts expanded the absorption bands at 3430 cm −1 (–OH), 1625 cm −1 (COOH), and 1082 cm −1 (C–O), confirming the interaction of ceria and ZnO with these functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc oxide (ZnO), as an admirable semiconductor material, also has attracted great attention in numerous applications, such as piezoelectric devices, sensors, transparent electronics, optics, optoelectronics, and actuators (Arya et al., 2012; Dastkhoon et al., 2015; Farag et al, 2016; Mahmouda and Fouad, 2015). Moreover, in photocatalytic degradation of different dyestuff, ZnO exhibited better photocatalytic efficiency than TiO 2 , although the band gap energy of ZnO is the same as that of TiO 2 (∼3.2 eV) (Arya et al., 2012; Mahmouda and Fouad, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of photodegradation of MO azo dye estimated at the pH of 3.0, and the results of degradation efficiency was found to be in the order of ZnO–CX-A > ZnO–CX-B > ZnO > CX. This system was found to follow pseudo-first-order kinetics . Some of the significant health effects of dyes and heavy metal ions present in the effluent can be visualized from Figures a and b, respectively.…”
Section: Different Forms Of Carbon Xerogels and Their Application In ...mentioning
confidence: 94%
“…Photolysis, unlike photocatalytic degradation, refers to the phenomenon that light energy is directly or indirectly transferred to chemical bonds under the action of light. The molecules are then transformed into excited states and split or transformed [1][2][3][4][5][6]. In recent years, the photolysis of organic pollutants has attracted widespread attention since it could help pollution control [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%